Micropropagation of ginger (Zingiber officinale Rosc. cv Tambunan) - Teoh, Yan Ji (2016)
This study was conducted at the Tissue Culture Laboratory Faculty of Sustainable Agriculture in Universiti Malaysia Sabah, Sandakan, Sabah to investigate the effect of NAA and BAP hormones at different concentrations on in vitrogrowth of ginger (Zingiber officinale Rosc cv Tambunan). The experimental design was Complete Randomized Design (CRD) using 0 mg/L BAP and NAA as a control, BAP (1, 2 and 3 mg/L) and NAA (1, 2 and 3 mg/L) alone or combination of both for shoot regeneration, rooting and multiplication. Each of the treatment was replicated ten times and the observation was done every two weeks. Parameters such as number of shoots, number of leaves, number of roots, shoot and root length (cm), days to shoot initiation and survival rate (%) was calculated. The collected data was analyzed using SAS (Statistical Analysis Software) version 9.4 software. ANOVA with mean separation by Duncan's multiple range test (P < 0.05) was used to compare means of different treatments. Based on the result, 3 mg/L BAP and 1 mg/L NAA had Significantly induced the highest number of shoots (6.14 ± 0.91) after 10 weeks of culture and observed that the day to shoot initiation were shorter compared to other treatments. MS media supplemented with single hormone 2mg/L NAA achieved the highest number of root production (34.40 ± 1.81) with the highest root length at 4.52 ± 0.20 cm for root multiplication and elongation of axillary bud culture of Zingiber officinale Rosc. cv. Tambunan after 10 weeks of culture. Therefore, MS media supplemented with combination of 3 mg/L BAP and 1 mg/L NAA and single hormone treatment 2 m9/L NAA was recommended for better growth and development of Zingiber officinale Rosc. cv. Tambunan.